BELA NEGARA PERSPEKTIF ‘ALI JUM’AH (STUDI KITAB AMNU AL-MUJTAMA’ WA ISTIQRĀRUHU MIN MANẒŪRIN ISLĀMIYYIN) - Masruhin, Abdurrohiem (Syariah: Journal of Fiqh Studies, 2023)
The nationalism, which is directly proportional to the act of defending the country, is degraded for many years. In addition, there are efforts to place the interests of religion and the state in a vis a vis position. One of the modern ulama who provides a counternarrative on this issue is 'Ali Jum'ah. His capacity as someone who has served as Grand Mufti in Egypt makes his thoughts has an urgency to study For this reason, the study aims to analyze 'Ali Jum'ah's thoughts about defending the country in his book, Amnu Al-Mujtama' Wa Istiqrāruhū Min Manẓūrin Islāmiyyin. To achieve these objectives, the method used in this research is content analysis and is classified as a qualitative method whose use a descriptive analytics.. As a result, defending the country in the perspective of 'Ali Jum'ah based on the ideas in that book is all actions and efforts that integrate the political, social, civilization, economic, military and environmental and and contain four main principles justice (al-‘adalah), freedom (al-hurriyah), egalitarianism (al-musawah) and love (ar-rahmah). In the book, 'Ali Jum'ah also provides several models for contextualization of defending the country, the Makkah model, the Ethiopian model, the Medina model at the beginning of the hijrah period, and the Medina model at the end of the Prophet Muhammad's life.